A method of pipeline corrosion detection based on hoop‐strain monitoring technology. Issue 6 (30th August 2016) - Ren, Liang; Jiang, Tao; Li, Dong‐sheng; Zhang, Peng; Li, Hong‐nan; Song, Gang‐bing
Summary: A pipeline is often an important structure with very long service life. It is of great significance to monitor the corrosion level of a pipeline to ensure its safety operation. This paper aims to develop a new nondestructive method to detect the pipeline corrosion. It is assumed that the pipeline corrosion will result in a variation of the circumferential strain. The nondestructive detection method is based on a novel fiber Bragg grating (FBG) hoop‐strain sensor, which can accurately measure the circumferential strain of a pipeline. In this paper, the theoretical study and numerical analysis based on finite element method are detailed in our initial work. Then, tests are conducted on three steel pipes to verify the effectiveness and accuracy of this method. The results demonstrate that the FBG hoop‐strain sensor has good performance in the circumferential strain measurement and is sensitive to the variation of the circumferential strain caused by different corrosion level. The FBG hoop‐strain sensor is considered to be a promising device in pipeline corrosion monitoring. Copyright © 2016 John Wiley & Sons, Ltd.